Relationship of Work Satisfaction and Organizational Commitment: a Literature Review - Ali Mamat; Muhamad Kamel Ali (Jurnal Konseling dan Pendidikan, 2018)
The enjoyment of working in an organization contribute to a positive impact in life. This also can be related to the individual job satisfaction. In fact, the job satisfaction including six elements namely salary, promotion, supervisor, job environment, colleagues and working conditions. Consequently, this study aims to investigate and identify the factors which influence job satisfaction in an organization by using document analysis with reference to previous study. However , the findings reveal a few factors that support the relationship between job satisfaction and organizational commitment among primary school assistant teachers. This gives clarity about the relevance of the relationship between the theories used in this study.